Evaluasi Usability Dan Perbaikan Desain Antarmuka Aplikasi Info Pdam Tirta Satria Menggunakan Metode Use Questionnare - Hengky Wijaya; Endang Setyawati; Christy Mahendra (INCODING: Journal of Informatics and Computer Science Engineering, 2021)
PERUMDA Tirta Satria is a regional public company engaged in the distribution of water in Banyumas Regency. PERUMDA Tirta Satria has a mobile application called Info PDAM Banyumas. The number of complaints experienced by users while using Info PDAM Banyumas application is the main reason to test the usability of this application. The usability testing method used in this study uses the USE Questionnaire. The results of the usability level obtained from the test are 70.85% which fall into the Eligible or Good category. From the results obtained after the evaluation, it shows that there are usability problems found in the application, such as unclear text, a stiff and unattractive interface, disproportionately large icon sizes, uninformative help menus, and problems when the user make customer complaints because of the unclear flow. To answer the problems that exist in this study, researcher made improvement recommendations for the interface by using Google Material Design as the basis.